2009
DOI: 10.1007/s00432-008-0538-4
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of ribosomal protein L7A in human osteosarcoma

Abstract: Under-expression of RPL7A may be involved in the carcinogenesis of osteosarcoma. Loss of RPL7A expression may be associated with poor survival of osteosarcoma patients with lung metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In addition, it was reported that RPL7A expression was significantly down-regulated in OS tissues compared with that in normal bone tissues and benign bone lesions both in mRNA and protein levels. Low expression of RPL7A indicated a poor clinical outcome for overall survival in OS patients with lung metastasis at the time of initial diagnosis with primary OS41.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that RPL7A expression was significantly down-regulated in OS tissues compared with that in normal bone tissues and benign bone lesions both in mRNA and protein levels. Low expression of RPL7A indicated a poor clinical outcome for overall survival in OS patients with lung metastasis at the time of initial diagnosis with primary OS41.…”
Section: Discussionmentioning
confidence: 99%
“…RPL7a interacts with the human thyroid hormone receptor and inhibits transactivation. Hyperthyroidism favours osteosarcoma cell growth and down-regulation of RPL7a might enhance sensitivity to TR and disrupt growth control [61]. RPL18 was shown to inhibit autophosphorylation of the double-stranded RNA-activated protein kinase (PKR) and PKR mediated phosphorylation of the translation initiation factor eIF2α.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of L41 mRNA was detected in 75% of primary breast cancers . Downregulation of L7a is associated with a poorer survival of osteocarcinoma patients with lung metastasis . The S6 protein is highly expressed in diffuse large B‐cell lymphomas (DLBCL), and knockdown of S6 leads to decreased proliferation of these cells in culture .…”
Section: The Potential Value Of Ribosomal Proteins In the Diagnosis Amentioning
confidence: 99%